Determination of optimal ratio of freund's incomplete and palm oil adjuvants incorporated into feed-based oral vaccine for fish - Aminudin, Sa'aidatun Asyikin (2017)
Adjuvant plays an important role in the effectiveness of vaccines. It causes slow release of the vaccine thus, inducing long-term protection in animals and man. Optimal ratio of the adjuvant to be added must be determined to ensure optimal effect. In this study, two different adjuvants were compared in the newly developed feed-based vaccine against streptococcosis to determine the optimal ratio of adjuvant. They were the Freund’s incomplete adjuvant (FIA) and the palm oil adjuvant (POA). The ratios were 0%, 3%, 5%, 7% and 10% adjuvants. 500 red hybrid tilapia of approximately 100g ± 10g bodyweight were divided into 5 groups for FIA and 600 red hybrid tilapia in 6 treatment groups for POA. Each replicate was vaccinated with double booster regime (3 vaccinations) using Feed Adjuvanted Vaccine (FAV) on weeks 0, 2 and 6. Other than that, normal commercial feeds were given. On week 10, the fish were challenged intraperitoneally with 2.6 x 10 9 CFU/mL of live Streptococcus agalactiae. Serum samples collected at weekly intervals from all replicates for a period of sixteen weeks were subjected to ELISA to determine the systemic antibody responses. Immunization by FAV resulted in significant (p<0.05), p= 0.032 increase in the serum antibody levels (IgM) as early as week 2 in all vaccinated groups, while the level in the control group was insignificant (P>0.05), p=0.134. Groups with 5% to 10% adjuvants showed highest antibody levels. In fact, the antibody response of 7% and 10% showed no significance difference. In general, the 10% ratio of palm oil adjuvant stimulated better systemic immune responses resulting in good protection with 70% survival rate after challenge. Thus, the 10% palm oil ratio is the adjuvant of choice as the price is cheaper and easily available in Malaysia compared to Freund’s incomplete adjuvant and at the same time gives good protection level to the fish.